2011
DOI: 10.1186/1750-9378-6-21
|View full text |Cite
|
Sign up to set email alerts
|

High-risk HPV infection after five years in a population-based cohort of Chilean women

Abstract: BackgroundThe need to review cervical cancer prevention strategies has been triggered by the availability of new prevention tools linked to human papillomavirus (HPV): vaccines and screening tests. To consider these innovations, information on HPV type distribution and natural history is necessary. This is a five-year follow-up study of gynecological high-risk (HR) HPV infection among a Chilean population-based cohort of women.FindingsA population-based random sample of 969 women from Santiago, Chile aged 17 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
2
12
0
2
Order By: Relevance
“…We designed a multicentre case–control study based upon the IARC biobank of HPV16-positive samples, with additional supplementation of HPV16-positive samples derived from cervical screening programmes in Italy (Sideri et al , 2009; Del Mistro et al , 2010) and Chile (Ferreccio et al , 2011). Cases were defined as women with HPV16-positive histologically confirmed cervical cancer, whereas controls included women with HPV16-positive normal cytology, atypical squamous cells of unknown significance or low-grade squamous intra-epithelial lesions.…”
Section: Methodsmentioning
confidence: 99%
“…We designed a multicentre case–control study based upon the IARC biobank of HPV16-positive samples, with additional supplementation of HPV16-positive samples derived from cervical screening programmes in Italy (Sideri et al , 2009; Del Mistro et al , 2010) and Chile (Ferreccio et al , 2011). Cases were defined as women with HPV16-positive histologically confirmed cervical cancer, whereas controls included women with HPV16-positive normal cytology, atypical squamous cells of unknown significance or low-grade squamous intra-epithelial lesions.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple HPV type infections that include HPV-18 form 47% of HPV infections in Colombia, and 56% in Peru, which are higher than worldwide incidence at 20% [22]. From 2001 to 2006 prevalence of HPV-16 and -18 increased from 2.6% to 6.1% in a cohort of 576 low socio-economic status Chilean females ranging from 17-to older than 70-years-old [27]. Consistent with this, from 2012 to 2016 in seven centers in Santiago, dependent upon population subgroup, the combined prevalence of HPV-16 and HPV-18 in cervical cytology ranged from 3.2% to 7.6% [28,29].…”
Section: Population Specific Prevalence and Sequela Of Hpv In The Andmentioning
confidence: 99%
“…A population-based survey of adult Chilean women reported an overall prevalence of HR-HPV genital infection (any oncogenic type) of 15%, with the highest prevalence observed in women under 25 years old [7]. A subsequent study confirmed that, among women in Santiago, Chile, cervical infection with HR-HPV peaks at young ages (< 20 years old) and then steadily decreases to stabilize around age 40 years, and increases again after age 60 years [8]. …”
Section: Introductionmentioning
confidence: 99%